Screen time reduction and Surya Namaskars—a comprehensive intervention for nonspecific back pain in adolescents: a study protocol - Oka, Gauri A.; Ranade, Ashish S.; Shinde, Mayur K.; Pore, Prasad D. (Frontiers in Pediatrics, 2025)
BackgroundStudies have shown that excessive screen time exposure and a lack of physical exercise are associated with nonspecific back pain in adolescents. Reduced screen time exposure and Surya Namaskars (Sun Salutations) have physical and psychological benefits. We aim to test a novel comprehensive school-based intervention module—Screen time reduction and Surya Namaskars (SanSKAR) for reducing the proportion of school-going adolescents reporting nonspecific back pain. The word “sanskar” originates in Sanskrit and roughly means good values or actions.MethodsThe study will be conducted in one of the six geographic divisions of a state in western India. 540 adolescent students from randomly selected urban and rural schools across five districts of this division will be included after informed assent and parental consent. Students’ heights, weights, school bag weights, and the presence and characteristics of back pain will be recorded with an on-site clinical examination by a pediatric orthopedic surgeon to rule out specific causes. Those with nonspecific back pain will perform SanSKAR: at least 12 Surya Namaskars daily at least five days a week for 16 weeks with screen time exposure of not more than 60 min per day. Post-intervention outcomes (proportion of students with back pain and its severity) will be measured at 8 weeks and 16 weeks.DiscussionThis study will help test a novel multipronged school-based intervention for back pain in adolescents. The results could inform practice changes for nonspecific back pain in school-going adolescents.Clinical Trial Registrationidentifier (CTRI/2024/07/070522).